(untitled) (IAHS Medical Journal, 2022)
Background : Coronavirus Disease 19 (COVID-19) is a novel coronavirus infection that has a wide spectrum of disease severity.The COVID-19 pandemic has posed several challenges to breastfeeding mothers. Prevention of COVID-19 transmission to newborns is one of the basic components of perinatal care in the era of the COVID-19 pandemic. Among many queries during pregnancy, to breastfeed or not is an important question that needs to be answered. This survey was conducted to assess the awareness towards COVID-19 including breastfeeding practices among lactating mothers during the COVID-19 pandemic. Materials and methods : This cross-sectional survey was conducted among lactating mothers whose baby was admitted in paediatric ward of Southern Medical College Hospital, Chattogram. The survey was conducted from July 2021 to November 2021. A total of 295 participants completed the survey. Results : Most of the participants (75.6%) reported close personal contact is the main route of COVID-19 transmission and 92.5% reported fever and cough is the common symptoms of COVID-19. Before breastfeeding maximum mothers(91.5%) sanitized their hand, but 57.2% mothers are reluctant to wear face mask. Only 37.3% lactating mothers opined that SARS-CoV-2cannot be transmitted through breastmilk. More than half of the participants (59.0%) states that they would stop breastfeeding if infected with COVID-19. Conclusion : This study demonstrates that the lactating mothers are aware of symptoms, mode of transmission and preventive measures of COVID-19. However, they are less aware of any guideline on breastfeeding during the COVID- 19 pandemic. More rigorous dissemination of information on breastfeeding practices in COVID-19 case management needs to be adopted. IAHS Medical Journal Vol 5(1), June 2022; 60-64